Method for preparing three-dimensional porous composite zinc electrode by electrostatic spinning method

By forming a protective film on the surface of the zinc negative electrode and forming a three-dimensional porous composite zinc electrode by electrospinning method, the problem of electrochemical performance degradation caused by zinc dendrites in the zinc electrode is solved, and a stable and flexible structure is achieved, suitable for renewable energy sources Energy storage applications.

CN119252840APending Publication Date: 2025-01-03QINGDAO UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411272328.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-11
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The electrochemical performance of zinc electrodes is degraded due to uncontrollable growth of zinc dendrites, which limits its practical application in renewable energy storage applications.

Method used

By forming a protective film on the surface of the zinc negative electrode, the zinc powder is woven into the filament by electrospinning, forming a three-dimensional porous composite zinc electrode, inhibiting the generation of dendrites and uniformly depositing zinc ions, reducing direct contact with the aqueous electrolyte solution .

Benefits of technology

A stable three-dimensional porous composite zinc electrode structure is realized, reducing the volume changes in the generation of zinc branches and charging and discharging, improving electrochemical performance and flexibility, and is suitable for flexible battery applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119252840A_ABST
    Figure CN119252840A_ABST
Patent Text Reader

Abstract

The invention relates to a method for preparing a three-dimensional porous composite zinc electrode through an electrostatic spinning method, and belongs to the technical field of zinc ion batteries. A layer of film is generated on the surface of a zinc negative electrode through a chelating agent, and the film has rich functional groups, rich active sites, simple synthesis method and strong affinity to zinc ions, can guide the zinc ions to be uniformly deposited on an electrostatic spinning material, and relieves volume change in the charge-discharge process; then the composite zinc electrode is woven into fiber filaments through electrostatic spinning to form a three-dimensional porous electrode, so that the formed electrode is stable and flexible in structure, direct contact with an aqueous electrolyte can be effectively reduced, and generation of zinc crystal dendrites and volume change in the charging and discharging process are inhibited.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a three-dimensional porous composite zinc electrode by an electrostatic spinning method, belonging to the technical field of zinc ion batteries. Background Art

[0002] With the pollution of the environment and the demand for energy, renewable energy (solar energy, wind energy) has attracted people's attention and development. Aqueous zinc-based batteries are considered to be promising candidates for large-scale energy storage. The zinc metal anode has a low redox potential (-0.76V), a high theoretical capacity (820mAh g -1 or 5855mAh cm -3 ), and has been widely studied due to its abundant resources, low cost, green and safe. Among them, zinc powder has better reaction activity than zinc metal, and zinc powder as an anode has outstanding advantages in cost, large-scale processing and adjustability. However, the electrochemical performance of zinc electrode is greatly reduced due to the uncontrollable zinc dendrite growth, which also limits its practical application. Therefore, in the method of improving the electrochemical performance of zinc negative electrode, constructing a stable zinc protection interface has become the research focus in this field. Summary of the invention

[0003] Based on the above problems that occur in the zinc negative electrode, the present invention provides a method for preparing a three-dimensional porous composite zinc electrode by electrospinning. First, a protective film is treated by reaction on the surface of the zinc negative electrode to inhibit the generation of dendrites and guide the uniform deposition of zinc ions. Then, zinc powder is spun into filaments by electrospinning to form a three-dimensional network. It is easy to realize industrial production.

[0004] In order to achieve the above requirements, the first technical solution of the present application discloses a method for preparing a three-dimensional porous composite zinc electrode by electrospinning, comprising the following steps:

[0005] S1. Preparation of zinc powder electrode substrate: placing zinc powder in a chelating agent to undergo spontaneous etching reaction;

[0006] S2. Preparing an electrospinning material: dissolving and diluting polyacrylonitrile, polyvinylidene fluoride, and carbon nanotubes, respectively, and then mixing to obtain a mixed solution; namely, an electrospinning material;

[0007] S3. Preparing an electrospinning solution: adding the zinc powder electrode substrate described in S1 to the mixed solution to uniformly disperse the zinc powder electrode substrate to obtain an electrospinning solution;

[0008] S4. Preparation of composite zinc electrode: The electrospinning solution is subjected to electrospinning to obtain a three-dimensional porous composite zinc electrode.

[0009] Furthermore, the chelating agent described in S1 is one or more of ethylenediaminetetramethylenephosphonic acid, aminotrimethylenephosphonic acid, nitrilotriacetic acid, ethylenediaminetetraacetic acid, ethylenediaminetetraacetic acid sodium salt, citric acid, and tartaric acid.

[0010] Furthermore, the concentration of the chelating agent solution in S1 is 0.05-0.5 wt %.

[0011] Furthermore, the spontaneous etching reaction processing time in S1 is 5-50 minutes.

[0012] Furthermore, based on 100% of the total mass, the amount of polyacrylonitrile, polyvinylidene fluoride, carbon nanotubes, and zinc powder electrode substrate added is:

[0013] Polyacrylonitrile: 5%-20%;

[0014] Polyvinylidene fluoride: 5%-20%;

[0015] Carbon nanotubes: 1%-15%;

[0016] Zinc powder electrode substrate: 40%-80%.

[0017] Furthermore, the solvent for dissolving polyacrylonitrile, polyvinylidene fluoride and carbon nanotubes in S2 is dimethyl diamide.

[0018] Furthermore, in the electrospinning method described in S4, the electrospinning syringe is connected to a No. 15 needle, the forward speed is 0.005-0.020 ml / min, the voltage between the needle and the receiving plate is 15-25 kV, and the spacing is 20 cm.

[0019] Also, the composite zinc electrode prepared according to the above preparation method and its application as an electric negative electrode in a flexible battery.

[0020] Compared with the prior art, the present invention has the following advantages: the present invention generates a thin film on the surface of the zinc negative electrode through a chelating agent, the thin film has rich functional groups, rich active sites, a simple synthesis method, and a strong affinity for zinc ions, which can guide the zinc ions to be uniformly deposited on the electrospinning material and alleviate the volume change during the charge and discharge process; then the composite zinc electrode is woven into the fiber filaments through electrospinning to form a three-dimensional porous electrode, so that the formed electrode structure is stable and flexible, which can effectively reduce direct contact with the aqueous electrolyte, inhibit the generation of zinc dendrites and the volume change during the charge and discharge process. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a picture of the actual object obtained by electrospinning in Example 1 of the present invention.

[0022] Figure 2This is a flexibility test diagram of the electrode obtained by electrospinning in Example 1 of the present invention.

[0023] Figure 3 It is a scanning electron microscope image of the composite electrode obtained by electrospinning in Example 1 of the present invention.

[0024] Figure 4 The 1000 mAg of the zinc-iodine battery assembled in the (1 m ZnSO4) electrolyte obtained in Example 1 of the present invention -1 Charge and discharge curves under current density.

[0025] Figure 5 The 1000 mAg of the zinc-iodine battery assembled in the (1 m ZnSO4) electrolyte obtained in Example 1 of the present invention -1 Cycling performance diagram at different current densities. DETAILED DESCRIPTION

[0026] The present invention is further described in detail below in conjunction with specific examples. This implementation case is implemented based on the technology of the present invention, and a detailed implementation method and specific operation process are now given to illustrate that the present invention is creative, but the protection scope of the present invention is not limited to the following examples.

[0027] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.

[0028] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.

[0029] The embodiment of the present application provides a method for preparing a three-dimensional porous composite zinc electrode by electrospinning, comprising the following steps:

[0030] S1. Preparation of zinc powder electrode substrate: placing zinc powder in a chelating agent to undergo spontaneous etching reaction;

[0031] S2. Preparing an electrospinning material: dissolving and diluting a mixture of polyacrylonitrile and polyvinylidene fluoride and carbon nanotubes, respectively, and then mixing to obtain a mixed solution, i.e., an electrospinning material;

[0032] S3. Preparing an electrospinning solution: adding the zinc powder electrode substrate described in S1 to the mixed solution to uniformly disperse the zinc powder electrode substrate to obtain an electrospinning solution;

[0033] S4. Preparation of composite zinc electrode: The electrospinning solution is subjected to electrospinning to obtain a three-dimensional porous composite zinc electrode.

[0034] It can be understood that in the embodiment of the present application, in order to reduce impurities on the surface of the zinc powder, the zinc powder is repeatedly cleaned with distilled water and alcohol before being placed in the chelating agent. And after the chelating agent treatment, the surface of the zinc powder electrode substrate is cleaned with distilled water to remove excess acid, etc., which are all within the general knowledge of those skilled in the art and are not particularly limited in the present application.

[0035] In the embodiment of the present application, the purpose of adding the chelating agent is to cause a spontaneous etching reaction on the surface of the zinc powder to form a thin film on the surface of the zinc powder, which is rich in functional groups and thus has abundant active sites, thereby increasing the affinity between the zinc powder and the interface protective layer.

[0036] In a further embodiment, the chelating agent is preferably one or more of ethylenediaminetetramethylenephosphonic acid, aminotrimethylenephosphonic acid, nitrilotriacetic acid, ethylenediaminetetraacetic acid, ethylenediaminetetraacetic acid sodium salt, citric acid, and tartaric acid. These acids can react with zinc powder to spontaneously etch on the surface, and their rich functional groups can improve the affinity between zinc powder and the interface protective layer.

[0037] In some preferred embodiments, the concentration of the chelating agent solution is 0.05-0.5 wt %; and the spontaneous etching reaction treatment time is 5-50 min.

[0038] In this embodiment, due to the strong interaction between the chelating agent and the metal, the solution solubility of the chelating agent should be controlled in a relatively low range (0.05-0.5wt% range in the present application). Too high a concentration is likely to have a bad effect on the material itself, such as damaging the electrode itself; and relatively speaking, a lower concentration can regulate the thickness of the formed film by time; in addition, within the concentration range specified in the present application, the reaction treatment time needs to be controlled at 5-50min, because the length of time can control the thickness of the formed film. If the time is short, the crystallization is poor, and thus the functional groups are fewer, so the affinity for zinc ions is limited. Conversely, if the time is too long, the formed film will be very thick or uneven, affecting the conductivity and increasing the resistance of the battery.

[0039] It can be understood that in the mixing process described in S2, in order to improve the uniformity of the mixing and the dispersion effect of the zinc powder, it is preferably stirred under ultrasonic conditions.

[0040] In the embodiment of the present application, the electrospinning material has a strong affinity for the zinc powder electrode substrate, and can isolate the zinc powder with the thin film generated by the chelating agent, effectively preventing the zinc powder from generating dendrites, while also guiding the uniform deposition of zinc ions and alleviating volume changes during the charge and discharge process.

[0041] In some specific embodiments, based on 100% of the total mass, the amount of the polyacrylonitrile and polyvinylidene fluoride mixture, carbon nanotubes, and zinc powder electrode substrate added is:

[0042] Polyacrylonitrile: 5%-20%;

[0043] Polyvinylidene fluoride mixture: 5%-20%;

[0044] Carbon nanotubes: 1%-15%;

[0045] Zinc powder electrode substrate: 40%-80%.

[0046] In some specific embodiments, the solvent for dissolving the mixture of polyacrylonitrile and polyvinylidene fluoride and the carbon nanotubes in S2 is dimethyl diamide.

[0047] In some specific embodiments, in the electrospinning method described in S4, the electrospinning syringe is connected to a No. 15 needle, the forward speed is 0.005 to 0.020 ml / min, the voltage between the needle and the receiving plate is 15 to 25 kV, and the spacing is 20 cm.

[0048] In this embodiment, electrospinning weaves the composite zinc electrode into the fiber filaments to form a three-dimensional porous electrode, so that the formed electrode structure is stable and flexible, which can further effectively reduce the direct contact with the aqueous electrolyte, further inhibit the generation of zinc dendrites and volume changes during charging and discharging.

[0049] The following examples are provided for a better understanding and explanation of the present invention and are not intended to limit the best processing methods and experimental schemes.

[0050] Example 1 Preparation of composite zinc electrode

[0051] S1. Prepare zinc powder electrode substrate: prepare 0.1%wt chelating agent with ethylenediaminetetramethylenephosphonic acid, and soak the cleaned zinc powder in the chelating agent for 15 minutes to obtain zinc powder electrode substrate, and wash away excess acid on the surface of the zinc powder electrode substrate with distilled water for standby use.

[0052] S2. Preparation of electrospinning materials: Dissolve 0.3 g of polyacrylonitrile and polyvinylidene fluoride (PVDF / PAN) in 3 ml of dimethylformamide and stir for 30 min, then add 0.2 g of carbon nanotubes to 0.6 ml of dimethylformamide and stir quickly to make them uniformly dispersed. Add the carbon nanotube solution to the polyacrylonitrile solution and stir evenly, then add the polyvinylidene fluoride solution to the above mixture and stir for 30 min.

[0053] S3. Prepare electrospinning solution: add 2.4 g zinc powder electrode substrate to the mixed solution, stir to mix evenly, ultrasonicate for 30 min, and then stir for 2 to 3 h for standby use.

[0054] S4. Preparation of composite zinc electrode: Use a 10ml syringe connected to a 15-gauge needle, set the forward speed to 0.016ml / min, the voltage between the needle and the receiving plate to 22kv, and the distance between the two to 20cm. Use electrospinning to spin the mixed spinning solution into a three-dimensional porous composite electrode, in which zinc powder is evenly dispersed in the filaments of polyacrylonitrile and polyvinylidene fluoride (PVDF / PAN), to obtain a composite zinc electrode.

[0055] Attached Figure 1 , 2 3 are the physical image, flexibility image and scanning electron microscope image of the zinc electrode prepared in this embodiment. It can be seen from the figure that the zinc electrode prepared by the present application overcomes the rigidity of the traditional zinc metal negative electrode and is transformed into a flexible material ( Figure 2 ), which is of great significance for future smart wearables; through scanning electron microscopy ( Figure 3 ) It can be seen that the zinc powder is evenly distributed in the filaments of polyacrylonitrile and polyvinylidene fluoride (PVDF / PAN), thus completing the transition from zinc metal (rigid) to this electrospun flexible electrode, making the zinc negative electrode flexible.

[0056] Example 2 Preparation of composite zinc electrode

[0057] S1. Prepare zinc powder electrode substrate: configure citric acid as 0.3%wt chelating agent, and soak the cleaned zinc powder in the chelating agent for 5 minutes to obtain a zinc powder electrode substrate, and wash away excess acid on the surface of the zinc powder electrode substrate with distilled water for standby use.

[0058] S2. Preparation of electrospinning materials: Dissolve 0.5 g of polyacrylonitrile and polyvinylidene fluoride (PVDF / PAN) in 5 ml of dimethylformamide and stir for 30 min, then add 0.3 g of carbon nanotubes to 0.9 ml of dimethylformamide and stir quickly to make them uniformly dispersed. Add the carbon nanotube solution to the polyacrylonitrile solution and stir evenly, then add the polyvinylidene fluoride solution to the above mixed solution and stir for 30 min.

[0059] S3. Prepare electrospinning solution: add 2.7g zinc powder electrode substrate to the mixed solution, stir to mix evenly, ultrasonicate for 30min, and then stir for 2-3h for standby use.

[0060] S4. Preparation of composite zinc electrode: Use a 10ml syringe connected to a 15-gauge needle, set the forward speed to 0.005ml / min, the voltage between the needle and the receiving plate to 15kv, and the distance between the two to 20cm. Use electrospinning to spin the mixed spinning solution into a three-dimensional porous composite electrode, in which zinc powder is evenly dispersed in the filaments of polyacrylonitrile and polyvinylidene fluoride (PVDF / PAN), to obtain a composite zinc electrode.

[0061] Example 3 Preparation of composite zinc electrode

[0062] S1. Prepare zinc powder electrode substrate: prepare 0.5%wt nitrilotriacetic acid as chelating agent, and soak the cleaned zinc powder in the chelating agent for 50 minutes to obtain zinc powder electrode substrate, and wash away excess acid on the surface of the zinc powder electrode substrate with distilled water for standby use.

[0063] S2. Preparation of electrospinning materials: Dissolve 0.3 g of polyacrylonitrile and polyvinylidene fluoride (PVDF / PAN) in 3 ml of dimethylformamide and stir for 30 min, then add 0.2 g of carbon nanotubes to 0.6 ml of dimethylformamide and stir quickly to make them uniformly dispersed. Add the carbon nanotube solution to the polyacrylonitrile solution and stir evenly, then add the polyvinylidene fluoride solution to the above mixture and stir for 30 min.

[0064] S3. Prepare electrospinning solution: add 1.2 g zinc powder electrode substrate to the mixed solution, stir to mix evenly, ultrasonicate for 30 min, and then stir for 2 to 3 h for standby use.

[0065] S4. Preparation of composite zinc electrode: Use a 10ml syringe connected to a 15-gauge needle, set the forward speed to 0.020ml / min, the voltage between the needle and the receiving plate to 25kv, and the distance between the two to 20cm. Use electrospinning to spin the mixed spinning solution into a three-dimensional porous composite electrode, in which zinc powder is evenly dispersed in the filaments of polyacrylonitrile and polyvinylidene fluoride (PVDF / PAN), to obtain a composite zinc electrode.

[0066] Test Example 1 Performance Test

[0067] The composite zinc electrode prepared in Example 1 was used to assemble a zinc-iodine battery in a 1 m ZnSO4 electrolyte. The iodine loading in the carbon cloth was (3 mg cm -2 ), and then at 1000mAg -1 Charge-discharge curves and cycle performance under current density (10 activation cycles).

[0068] The experimental results are as follows Figure 4 and Figure 5As shown: the composite zinc electrode prepared by the technical solution of this application can realize normal charging and discharging, and has a certain stability, that is, the zinc electrode has the same charging and discharging performance as the general rigid zinc electrode; at the same time, because the zinc electrode can be bent and has a certain elastic deformation, it can be applied to some flexible devices and smart wearables, and unlike general metal electrodes, if compressed and folded, it cannot be restored to its original shape. Finally, for energy storage devices, the application of flexible devices is still better than that of rigid devices, and has certain advantages in carrying and other aspects.

Claims

1. A method for preparing a three-dimensional porous composite zinc electrode by electrospinning, characterized in that: The following steps are involved: S1. Preparation of zinc powder electrode substrate: placing zinc powder in a chelating agent to undergo spontaneous etching reaction; S2. Preparing an electrospinning material: dissolving and diluting polyacrylonitrile, polyvinylidene fluoride, and carbon nanotubes, respectively, and then mixing to obtain a mixed solution, i.e., an electrospinning material; S3. Preparing an electrospinning solution: adding the zinc powder electrode substrate described in S1 to the mixed solution to uniformly disperse the zinc powder electrode substrate to obtain an electrospinning solution; S4. Preparation of composite zinc electrode: The electrospinning solution is subjected to electrospinning to obtain a three-dimensional porous composite zinc electrode.

2. The preparation method according to claim 1, characterized in that: S1 The chelating agent is one or more of ethylenediaminetetramethylenephosphonic acid, aminotrimethylenephosphonic acid, nitrilotriacetic acid, ethylenediaminetetraacetic acid, ethylenediaminetetraacetic acid sodium salt, citric acid, and tartaric acid.

3. The preparation method according to claim 1, characterized in that: The concentration of the chelating agent solution in S1 is 0.05-0.5 wt %.

4. The preparation method according to claim 1, characterized in that: The spontaneous etching reaction treatment time in S1 is 5-50 minutes.

5. The preparation method according to claim 1, characterized in that: Based on 100% of the total mass, the amount of polyacrylonitrile, polyvinylidene fluoride, carbon nanotubes, and zinc powder electrode substrate added is: Polyacrylonitrile: 5%-20%; Polyvinylidene fluoride: 5%-20%; Carbon nanotubes: 1%-15%; Zinc powder electrode substrate: 40%-80%.

6. The preparation method according to claim 1, characterized in that: The solvent for dissolving polyacrylonitrile, polyvinylidene fluoride and carbon nanotubes in S2 is dimethyl diamide.

7. The preparation method according to claim 1, characterized in that: In the electrospinning method described in S4, the electrospinning syringe is connected to a No. 15 needle, the forward speed is 0.005-0.020 ml / min, the voltage between the needle and the receiving plate is 15-25 kV, and the spacing is 20 cm.

8. A composite zinc electrode prepared according to any one of the preparation methods of claims 1-7.

9. Use of the composite zinc electrode as claimed in claim 8 as an electric negative electrode in a flexible battery.